The Influential Factors in the Job Motivation among Midwives as the Healthcare Providers in the Iranian Health Sector Evolution Plan - P Masoumi Ganjgah; M Geranmayeh; SH Haghani (Iran University of Medical Sciences, 2020)
Background & Aims: Midwives play a key role in the delivery of care services to mothers and neonates in the health system. The provision of high-quality services by midwives has a great impact on the prevention of maternal and neonatal mortality and its consequences, as well as the empowerment of women. It has been recommended that countries expand their midwifery programs, maintain the highest global standards, and improve the environment where midwives could effectively address the needs of women and their families. To achieve these goals, it is essential to motivate midwives as high job motivation could promote their efficiency. Theorists consider several factors to be influential in job motivation, such as physiological needs, safety, social needs, respect, and self-actualization. In Herzbergchr('39')s two-factor theory, the needs and stimuli that motivate employees have been listed, as well as the approaches through which they could be addressed in an organization. Numerous studies have assessed the influential factors in the job motivation of midwives in Iran based Herzbergchr('39')s theory. Meanwhile, midwives in healthcare centers have exclusively focused on their job duties (i.e., care of women of the reproductive age, pregnant women, and neonates). It seems that some of the motivational dimensions proposed for midwives have been modified due to the changes in the job duties of healthcare midwives in the Health Sector Evolution Plan, in which all midwives have been regarded as healthcare midwives, their organizational position has changed, and they were obliged to provide non-specialized and non-midwifery services in addition to specialized midwifery services, such as care services for infectious and non-communicable diseases for all ages and genders. Since the influential factors in the job motivation of midwives have not been properly recognized after the Health Sector Evolution Plan, the present study aimed to determine the influential factors in the job motivation of midwives based on Herzbergchr('39')s theory. Materials & Methods: This descriptive, cross-sectional study was conducted on 207 midwives employed in the health centers affiliated to Tehran University of Medical Sciences (TUMS), located in the south of Tehran, Iran during in October-December 2018. The participants were selected via stratified sampling. Since TUMS covers three health networks of the south, Islamshahr, and Shahreray, each health network was selected as a stratified rank. Based on the population of the midwives of each rank and considering an average of two midwives per each health center, 120 health centers (south=60 bases, Islamshahr=25 bases, Shahreray=35 bases) were selected using a random numbers table for sampling. Data were collected using the standard Herzberg questionnaire and two open-ended questions regarding job motivation and intention to continue the profession after the Health Sector Evolution Plan. The quantitative data were analyzed in SPSS version 16 using descriptive statistics (independent t-test, analysis of variance, and Pearsonchr('39')s correlation-coefficient). In addition, the qualitative data were analyzed by content analysis. Results: In the responses to the internal factors in Herzbergchr('39')s job motivation questionnaire, the highest score belonged to the nature of the job (mean: 2.86±1.01), and the lowest score belonged to recognition (mean: 2.10±0.93). Among the extrinsic factors, the highest score belonged to the interactions of colleagues (mean: 3.99±0.76), while the lowest score belonged to salary and income (mean: 1.65±0.94). Furthermore, work experience prior to the Health Sector Evolution Plan (P=0.027) and work experience after the plan (P<0.001) had significant, inverse correlations with the internal factors. Work experience before the plan (P=0.016; r=-0.167) and work experience after the plan (P=0.001; r=-0.239) also had significant, inverse correlations with the internal factors, so that increased age and work experience before and after the plan led to the reduction of the mean scores of these factors. In addition, employment status had a significant association with the internal factors (P=0.004), so that the mean score of the internal factors in the corporate midwives was significantly higher than the formal and contractual midwives. Significant associations were observed between the work experience before the plan (P=0.037) and work experience after the plan (P<0.001) with the external factors. In addition, work experience before the plan (P=0.036 and P=-0.146) and work experience after the plan (P=0.036 and P=-0.146) had inverse, significant correlations with the external factors, and the increment in these variables led to reduced scores of the external factors. In addition, age had a significant correlation with the external factors (P=0.035), and the mean scores of these factors were significantly lower in the subjects aged more than 40 years compared to the mean scores of those aged less than 40 years. The majority (81.1%) of the midwives who answered the open-ended questions about changing job motivation (first open-ended question) reported that their job motivation has decreased compared to before the implementation of the evolution plan, and more than half of the midwives who answered the open-ended question about the continuation of the job as a healthcare midwife were willing to quit. Conclusion: In general, the analysis of the responses to the open-ended questions indicated that low income, heavy workload, stress, and unrelated tasks to midwifery reduced job motivation and increased the tendency to quit in the healthcare midwives after the health evolution plan. Therefore, it is recommended that healthcare authorities attempt to enhance the motivation of midwives and guarantee the quality and maintenance of midwifery care by designing appropriate evaluation and motivational mechanisms, providing a payroll system based on workload (improving the external factors), defining the job position of family midwives in the health system as opposed to healthcare midwives, and the fundamental review of the job description and position of midwifery in the health system (enrichment of the midwifery profession). Furthermore, conducting research on the views and opinions of middle-range managers of the Health Sector Evolution Plan about staff motivation and the challenges in improving the quality of the healthcare services provided by midwives and healthcare providers could result in the inclusive assessment of the issues and challenges and adoption of comprehensive, practical, and effective strategies.